SUMBANGAN BAHASA INDONESIA TERHADAP PENGENDALIAN COVID-19 - Pranowo Pranowo (STKIP Siliwangi, 2020)
This research is a descriptive qualitative research with the approach of Pragmasemantic theory and Speech Act theory. Pragmasemantic theory is basically a theory used to study the use of language based on meanings that take into account the intralingual and extralingual contexts. Mean while, speech act theory is essentially a theory that wants to explain that each utterance always contains three elements, namely locution, illocution, and perlocution. The purpose of this study is (a) to describe the language functions that can be used to campaign for Covid-19 deployment control, (b) describe vocabulary that has touch power and can be used to campaign for Covid-19 deployment control, (c) describe language slogans that can used to campaign for Covid-19 deployment control, and (d) describe persuasive language forms that can be used to campaign for Covid-19 deployment control. Research data sources are students of the Indonesian Language and Literature Education Study Program, S1 and S2 programs which can be reached via online media, email or WA. Research data in the form of words, phrases, sentences that show the function of language, vocabulary that has the power of touch, slogans that can encourage, persuasive language that can persuade speech partners compiled by students. Data collection techniques are carried out by sending instruments via email or WA, then students are asked to fill out and send back to researchers. The collected data is then inventoryed and codified to determine incoming data that is suitable for analysis. The analysis techniques are (1) identifying data, (b) classifying data, (c) interpreting data with the intention of being able to interpret Covid-19 ways of controlling, and (d) preparing reports in the form of journal articles.